Effects of different application doses of black soldier fly frass Hermetia illucens (Diptera: Stratiomydae) on soybean plant performances and arthropod abundance (Asian Journal of Agriculture, 2024)
Abstract. Yudistira DH, Sandi YU, Wirabumi BA, Damayanti A, Wikandari P, Sato S. 2025. Effects of different application doses of black soldier fly frass Hermetia illucens (Diptera: Stratiomydae) on soybean plant performances and arthropod abundance. Asian J Agric 9: 40-51. Food waste poses a global challenge, contributing approximately 3.49 billion tons of CO2 to the atmosphere annually. Recycling this waste into valuable soil nutrients is a viable solution. This study focuses on black soldier fly Hermetia illucens L. (Diptera: Stratiomydae) larvae, which convert organic waste into protein-rich biomass and frass, a potential soil amendment. However, the effects of black soldier fly frass on crop performance and biodiversity remain underexplored. We investigated the impact of three different frass doses (0, 2.5, and 5 tons/ha) on the growth of the Tsuruoka soybean variety (Glycine max L.), dadachamame. Results showed no significant differences in plant height (p =0.07), but higher doses increased leaf count (p
Keywords: Biodiversity, food waste recycling, organic farming, sustainable agriculture, trophic interaction